2019
DOI: 10.1111/ijpp.12518
|View full text |Cite
|
Sign up to set email alerts
|

Competence, competition and collaboration: Perceived challenges among Swedish community pharmacists engaging in pharmaceutical services provision and research

Abstract: Background Creating evidence of effectiveness is an important part of service development. In an ongoing research project Swedish community pharmacists participate in services research by recruiting patients initiated on statins to an adherence‐promoting cognitive pharmaceutical service, jointly run by nurses and pharmacists. Aims To explore the pharmacists’ experiences of providing part of the service and their views regarding future participation in practice research aiming at developing cognitive pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…These evaluations can facilitate transformation to value-based care. Indeed, pharmacists readily recognize that evidence is needed to support practice advancement in the community setting [19,20]. Since clinically integrated networks of community pharmacies are forming in nearly every state across the United States, there is ample opportunity for more community pharmacy PBRNs to grow from these networks and assist with outcomes research [6].…”
Section: Discussionmentioning
confidence: 99%
“…These evaluations can facilitate transformation to value-based care. Indeed, pharmacists readily recognize that evidence is needed to support practice advancement in the community setting [19,20]. Since clinically integrated networks of community pharmacies are forming in nearly every state across the United States, there is ample opportunity for more community pharmacy PBRNs to grow from these networks and assist with outcomes research [6].…”
Section: Discussionmentioning
confidence: 99%
“…Competitive behavior is considered an aspect of human nature that is expressed in competition between business entities in the business environment which has been the subject of management research [14]. A study situated in Sweden identified high levels of competition among community pharmacists as a major barrier to collaborative focus on the patients' or customers' satisfaction [15]. A common form of competition among community pharmacists is price wars and discounting, a practice prevalent in developing countries.…”
Section: Competitive Behaviormentioning
confidence: 99%
“…Collaborative practices support quality service delivery and improve customer or patient engagement, and innovativeness [20]. A study of community pharmacists' services and collaboration in Sweden reveals low levels of collaborative behavior as a barrier to patientcentered pharmaceutical care [15,21].…”
Section: Collaborative Behavior Among Community Pharmacistsmentioning
confidence: 99%
“…Similarly, community pharmacists in France aim to use research projects to improve their practice, and develop new pharmacy services [22]. This perception is shared among Swedish community pharmacists, where research projects are viewed as means to promote community pharmacies to patients, and contribute to the development of new services [23]. However, community pharmacists often lack experience and feel uncomfortable with conducting such research due to perceived knowledge gaps.…”
Section: Knowledge and Interest Of French Community Pharmacists To Pa...mentioning
confidence: 99%